2012
DOI: 10.1143/jpsj.81.043702
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis of Iron-Based Superconductor FeSe Films

Abstract: The superconducting FeSe films were successfully fabricated using the electrochemical synthesis. The composition ratio of Fe and Se can be controlled by the electric potential and pH value. We found that the FeSe films deposited at the electric potential -1.75 V and pH 2.3 show the superconducting transition at 3.5 K. The establishment of this electrochemical synthesis technique will provide many advantages for application.Since the discovery of superconductivity in LaFeAsO 1-x F x 1 , several types of iron-ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Thin films were synthesized with other approaches such as metal-organic chemical vapor deposition (MOCVD) [29,30], molecular beam epitaxy (MBE) [31], and electrochemical synthesis [32]. In general it is found that β-FeSe 1-x Te x can be easily grown in a wide temperature range (250°C-600°C) on various substrates such as MgO, LaAlO 3 , SrTiO 3 , Si, SiO x /Si, GaAs, R-Al 2 O 3 , CaF2, and LSAT.…”
Section: C Fese 1-x Te X Thin Filmsmentioning
confidence: 99%
“…Thin films were synthesized with other approaches such as metal-organic chemical vapor deposition (MOCVD) [29,30], molecular beam epitaxy (MBE) [31], and electrochemical synthesis [32]. In general it is found that β-FeSe 1-x Te x can be easily grown in a wide temperature range (250°C-600°C) on various substrates such as MgO, LaAlO 3 , SrTiO 3 , Si, SiO x /Si, GaAs, R-Al 2 O 3 , CaF2, and LSAT.…”
Section: C Fese 1-x Te X Thin Filmsmentioning
confidence: 99%
“…Recently, very thick (thickness 100 µm) superconducting films of FeSe (T onset c = 8 K) were successfully deposited by electrochemical route [31].…”
Section: Synthesis Morphology and Crystalline Structurementioning
confidence: 99%
“…It was shown by scanning tunneling microscopy (STM) that this new kind of substrate can yield strain-free FeSe films. Very recently, Demura et al [31] demonstrated the growth of 100 µm thick films on metallic tapes by electrochemical route. In their preliminary work, the composition ratio of Fe and Se was controlled by electric potential ( figure 12) and pH value (figure 13).…”
Section: Fese X Filmsmentioning
confidence: 99%
“…Moreover, NiAs-type FeSe with ferrimagnetism often coexists and contaminates the superconducting β-FeSe in the products of the solid-state synthesis . Chemical methods such as metal organic chemical vapor deposition and electrochemical deposition have been applied to grow β-FeSe thin films and nanorod arrays . Superconducting β-FeSe nanocables, nanorods, nanoislands, and ultrathin films with several unit cells thickness on SrTiO 3 substrate provided possibilities for the fundamental understanding of reduced dimensionality on the enhanced T C .…”
Section: Introductionmentioning
confidence: 99%